Analisis Perbandingan Kinerja Teknik Modulasi BPSK dan QPSK Menggunakan Kanal Flat Slow Fading Pada Sistem CDMA - Fitri Amillia; Muhammad Erpan (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Code Division Multiple Access (CDMA) is one of the access technology used in communication systems and provide the radio interface solution that can accommodate a wide range of voice, data and multimedia with high speed. In this research, which represents a model simulation of CDMA communication system using BPSK and QPSK modulation techniques through a slow flat fading channels, then the model is simulated with Simullink Matlab 7.8.0. Test results CDMA system simulation BPSK and QPSK modulation techniques through a slow flat fading channels, such as the value of Bit Error Rate (BER) QPSK modulation technique produced better performance than BPSK modulation technique.